Teacher's Efforts and Practices to Ensure Learner Centeredness in English as a Foreign Language Classes Case of First Year EFL Master's Students at Mohamed-Cherif Messaadia University, Souk Ahras - Lamia Bouchrika (My University, 2022)
Abstract One of the main challenges teachers face is using the appropriate techniques and strategies to implement Learner- Centeredness (LC) in English Foreign Language (EFL) classes mainly because teachers may be do not engage cognitive and psychological side of students or the students do not have the necessary tools and are not ready enough to be the centre of the teaching learning process. Therefore, this study is an attempt to highlight teachers' main practices and efforts to implement LC approach (LCA) in Master classes, and to know to which extent these classes are learner centered. To achieve the research aims, an exploratory mixed approach to combine quantitative and qualitative data was used this research was conducted with 46 students belonging to first year Master's Degree at the Department of English at Mohamed Cherif Mesaadia University, Souk Ahras, and 04 teachers from the same department. To collect the necessary data to answer the research questions, a questionnaire was administered to students to check their level of readiness to be the center of the learning process, and an interview was done with teachers to find out about their teaching practices to ensure LC in EFL classes. The results obtained from the questionnaire show that most of master one EFL students are demotivated; they are not engaged in activities. Whereas, the results obtained from the interview show that EFL teachers face some challenges in implementing LCA such as the lack of materials and time, the overcrowded classes, and the most significant one is students' unwillingness and lack of readiness. According to the results we assert that LCA is not fully implemented in EFL classes due to some obstacles. -------------------- ملخص يواجه الأساتذة تحديات كبيرة لخلق التقنيات والاستراتيجيات المناسبة لتكريس منهج "المتعلم المتمركز" في تعلم اللغة الإنجليزية كلغة أجنبية، حيث حاولنا في هذه الدراسة تسليط الضوء على أبرز التقنيات التي يعتمدها الأساتذة في القسم اتكاء على هذه المقاربة.حيث ركّزت هذه الدراسة على الأنشطة التعليمية دور المعلم، ودور المتعلم ، وذلك من أجل إعطاء إضافة لمفهوم العملية التعليمية. ولقد أجريت هذه الدراسة بجامعة "محمد الشريف مساعدية" بـ"سوق أهراس"، وذلك بمشاركة 46 طالبا وأربعة أساتذة. حيث اتبعنا المنهج الوصفي بشقيه الكمّي والنوعي، أين تم تقديم استبيان للطلبة من أجل الاطلاع على آرائهم حول هذا المنهج، كما أُجريت مقابلة مع الأساتذة للاطلاع على جهودهم المبذولة عند تطبيقهم لهذه المقاربة. ولقد تمثلت النتائج في أنّ طلبة اللغة الإنجليزية محبطون لعدم مشاركتهم في الأنشطة التعليمية ، كما أنّ الأساتذة يواجهون تحديات كبيرة في تطبيق منهجية المتعلم كمحور في العملية التعليمية في القسم، والمتمثلة في غياب الوقت والوسائل، ضخامة عدد الطلاب في القسم، والأهم من ذلك عدم استعدادهم لذلك. وعليه نظرا للنتائج المتوصل إليها، نرى أنه من الصعب تطبيقه. إذن من خلال جملة الإحصاءات المتحصل عليها نذهب إلى تأكيد صحة فرضيتنا الثانية فقط.